ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PETUGAS DALAM PENYEDIAAN BERKAS REKAM MEDIS RAWAT JALAN DI RUMAH SAKIT AWAL BROS PEKANBARU - Nur Maimun; Hozizah . (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Standard record of documents medical outpatient service is 10 minutes. Based on the study introduction using samples from 230 file medical record outpatient, shows that in providing file medical record outpatient average 20 minutes. The purpose of this research is to know the factors that deals with officer performance in the provision of a beam medical record outpatient. Using analysis cross bivariat table ( contingency ) between variables using analysis by using chi square test. The results of research Be seen that than 57 respondents factors knowledge relating to officer performance shows that value = 0,008 ( POR = 5,800 , the communication deals with the performance value = 0,011 ( POR = 5,111 ). The Conclusion this research factors exist relations knowledge and communication with officer performance in the delivery of file medical record outpatient